Pengaruh Promosi Digital Media Sosial Instagram Terhadap Keputusan Pembelian Paket Tour Paipai Leisure - Rama Prayuda Dinata; Namira Fitria; Saiful Romadon (Indo Publishing, 2026)
This study aims to determine the influence of Instagram social media digital promotion on the purchase decision of Paipai Leisure tour packages. The research is motivated by the increasing use of Instagram as a promotional platform in the tourism industry, requiring companies to provide attractive, informative, and interactive promotional content to influence consumers' purchase decisions. However, there are still consumers who have not followed Paipai Leisure's Instagram account or have never been exposed to its promotional content on the platform. Therefore, the effectiveness of digital promotion in influencing consumers' purchase decisions requires further investigation. This study employed a quantitative research method. The population consisted of consumers who had previously purchased Paipai Leisure tour packages, with a sample of 92 respondents. Data were collected through questionnaires, and the data were analyzed using simple linear regression analysis. The results indicate that Instagram social media digital promotion has a positive and significant effect on the purchase decision of Paipai Leisure tour packages. This is evidenced by the calculated t-value of 11.168, which is greater than the critical t-value of 1.66177, with a significance level of 0.000 < 0.05. Therefore, the research hypothesis is accepted. Furthermore, the coefficient of determination (R²) of 0.581 indicates that Instagram social media digital promotion explains 58.1% of the variation in consumers' purchase decisions, while the remaining 41.9% is influenced by other factors outside the scope of this study.